СУЧАСНІ ПРОБЛЕМИ ПРОВЕДЕННЯ ЕКСПЕРТИЗИ В АДМІНІСТРАТИВНОМУ СУДОЧИНСТВІ - Романюк, Мирослав Васильович (SUPREMANCE OF LAW, 2018)
The article analyzes the problems of legal regulation of the procedure of conducting expert assessments in the administrative proceedings of Ukraine. The necessity to improve the current legislation on the issues of independent examination is noted. In the course of the research, a wide arsenal of scientific research methods was used, which revealed the current problems of appointing and conducting independent judicial exams. Classifications of possible violations during the examination in the course of administrative proceedings are formulated, as well as a number of preventive measures to prevent violation of the current legislation during expert examination. A number of proposals have been formulated to improve the methods of preventing violations during expert examination in administrative proceedings.